Athletes with different habitual fluid intakes differ in hydration status but not in body water compartments - Francisco, R.; Jesus, F.; Nunes, C. L.; Cioffi, I.; Alvim, M.; Mendonca, G. V.; Lukaski, H.; Sardinha, L. B.; Silva, A. M (Scandinavian Journal of Medicine & Science in Sports, 2023)
Physiological differences have been reported between individuals who have habitual low (LOW) and high (HIGH) water intake (WI). The aims of this study were to explore body water compartments, hydration status, and fat-free mass (FFM) hydration of elite athletes exposed to different habitual WI. A total of 68 athletes (20.6 ± 5.3 years, 23 females) participated in this observational cross-sectional study. Total WI was assessed by seven-day food diaries and through WI, athletes were categorized as HIGH (n = 28, WI=40.0 mL/kg/d) and LOW (n = 40, WI=35.0 mL/kg/d). Total body water (TBW) and extracellular water (ECW) were determined by dilution techniques and intracellular water (ICW) as TBW-ECW. Hydration status was assessed by urine-specific gravity (USG) using a refractometer. Fat (FM) and FFM were assessed by dual-energy X-ray absorptiometry (DXA). The FFM hydration was calculated by TBW/FFM. The USG was statistically different between groups for females (LOW: 1.024 ± 0.003; HIGH: 1.015 ± 0.006; p = 0.005) and males (LOW: 1.024 ± 0.002; HIGH: 1.018 ± 0.005; p < 0.001). No differences between groups were detected in body water compartments and FFM hydration in both sexes (p > 0.05). Multiple regression showed that WI remains a predictor of USG regardless of FFM, age, and sex (ß = -0.0004, p < 0.01). We concluded that LOW athletes were classified as dehydrated through USG although their water compartments were not different from HIGH athletes. These results suggest that LOW athletes may expectedly maintain the body water compartments' homeostasis through endocrine mechanisms. Interventions should be taken to encourage athletes to have sufficient WI to maintain optimal hydration.